Evaluation of the Engineering Geology Practice Route Based on Multifactor Reliability Analysis - Xiaoming Zhao; Binbin Yang; Dongqi Tang (Geofluids)
Engineering geological practice and investigation are important measures for geological fluid and engineering geological research; the practice route has an important impact on the achievement of research objectives. In this study, the practice route is mainly affected by four primary indicators: abundance of geological resources, rationality of the practice route, effect of practice, and the accommodation conditions. The four primary indicators include 13 secondary indicators, and each secondary indicator can be divided into positive and negative random variables, which is the specific content of the evaluation. In order to collect the feedback data of participants on the practice route, a questionnaire was constructed based on indicators at all levels. According to the results of the questionnaire, the mean and standard deviation of each random variable are counted and the distribution law of probability density is fitted. A performance function is constructed to represent the approval status of participants for each indicator. Considering the influence of 26 random variables, a multifactor evaluation method for the engineering geology practice route is proposed based on the reliability analysis method. This method can be used to analyze the approval status of random factors, search for the shortcomings of the route, and provide an effective method to improve the rationality of the route. The conclusion shows that this study provides a solution to evaluate fuzzy problems in engineering geological practice, especially if the problems are difficult to be quantified through experiment or measurement.